PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS FLIPBOOK ONLINE PADA PELAJARAN AL-QUR’AN HADITS MATERI KEBENARAN PENURUNAN AL-QUR’AN DI KELAS X MADRASAH ALIYAH NEGERI (MAN) KOTA BATU - Miftah Hur Rahman Zh; Arief Ardiansyah; Mutiara Sari Dewi (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This research is a type of development research (R&D). This research was developed using the five step ADDIE development model which that include analysis, design, development, implementation/execution, and evaluation. The main purpose of this research is to produce a learning media product in the form of an online flipbook-based learning media in the Al-Qur'an Hadith lesson on the Truth of the Decline of the Qur'an. The specific purpose of this research is to find out how to develop an online flipbook media and find out the students' responses to the media that has been created. This online flipbook learning media product was created using the Flipbook Corporation application with the help of the Canva application, Kinemaster and Wordwall interactive games. Data collection techniques used by interviews, observation, questionnaires and documentation. Quantitative and qualitative data were analyzed using a Likert scale. This study resulted in learning media in the form of online flipbook-based learning media in Al-Qur'an Hadith lessons, the Truth of the Decline of the Qur'an. This media contains audio, text, games, videos and images. Based on the validation that has been carried out by material experts, media experts, and Al-Qur'an Hadith subject teachers, class X produces an average score of 3.96 with the